UPAYA ORANGTUA DALAM MEMFILTER TONTONAN BAGI ANAK USIA DINI - Rendy Setyowahyudi (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2023)
Watching that is not appropriate for the age of the child can have a bad impact on the child. Parents are the closest figure as long as the child is at home. For this reason, parents need to filter the shows that are watched by children. The purpose of this study is to describe the efforts of parents in filtering viewing for young children. The method used is descriptive. The research subjects were 3 parents who had early childhood. The collection of data used is observation, interviews and documentation. Test the validity of the data using triangulation. While data analysis uses the Miles & Huberman model with the stages of data collection, data presentation, reduction and drawing conclusions. The results show that parents have three ways to filter viewing for young children, namely direct supervision, observing program schedules and preparing applications that are appropriate for the child's age. The implication of this research is to contribute knowledge to parents who have young children to find out ways that can be used to filter children's viewing at home.